2016
DOI: 10.1210/en.2015-1740
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of KNDy Neurons Results in Hypogonadotropic Hypogonadism and Amplifies the Steroid-Induced LH Surge in Female Rats

Abstract: In the human infundibular (arcuate) nucleus, a subpopulation of neurons coexpress kisspeptin and neurokinin B (NKB), 2 peptides required for normal reproductive function. A homologous group of neurons exists in the arcuate nucleus of rodents, termed KNDy neurons based on the coexpression of kisspeptin, NKB, and dynorphin. To study their function, we recently developed a method to selectively ablate KNDy neurons using NK3-SAP, a neurokinin 3 receptor agonist conjugated to saporin (SAP). Here, we ablated KNDy ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
56
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 79 publications
7
56
1
1
Order By: Relevance
“…The pattern of kisspeptin expression in the ARC was more complex. Castration resulted in a considerable increase in the number of kisspeptin neurones in LP animals, confirming the observations in other species that kisspeptin neurones in the ARC in sexually active animals are a major target of negative sex steroid feedback in both male and female animals 10,[28][29][30][31][32]. Of note, our study showed a major difference in LP castrated animals compared to the study of Greiveset al 14 in which castration in LP animals did not result in higher numbers of kisspeptin neurones in the ARC.…”
supporting
confidence: 91%
“…The pattern of kisspeptin expression in the ARC was more complex. Castration resulted in a considerable increase in the number of kisspeptin neurones in LP animals, confirming the observations in other species that kisspeptin neurones in the ARC in sexually active animals are a major target of negative sex steroid feedback in both male and female animals 10,[28][29][30][31][32]. Of note, our study showed a major difference in LP castrated animals compared to the study of Greiveset al 14 in which castration in LP animals did not result in higher numbers of kisspeptin neurones in the ARC.…”
supporting
confidence: 91%
“…In support of this possibility, ablation of ARC kisspeptin neurones leads to atypical LH surge amplitude. 56,57 The present findings are also in agreement with a recent study demonstrating RFRP-3 suppression of ARC kisspeptin expression in free-cycling Syrian hamsters maintained in long photoperiods. 23 This same previous study found that hamsters injected with RFRP-3 in the afternoon, but not in the morning, exhibit suppression of LH concentrations when in proestrus.…”
Section: Discussionsupporting
confidence: 93%
“…Our results show that the expression of ARC Kiss1 mRNA co‐varies with circulating LH levels, with RFRP‐3 acting to reduce both Kiss1 mRNA expression and circulating concentrations of LH in the afternoon but not in the morning, consistent with this pathway of control. In support of this possibility, ablation of ARC kisspeptin neurones leads to atypical LH surge amplitude . The present findings are also in agreement with a recent study demonstrating RFRP‐3 suppression of ARC kisspeptin expression in free‐cycling Syrian hamsters maintained in long photoperiods .…”
Section: Discussionsupporting
confidence: 93%
“…One intriguing speculation is that SCN inputs to ARN KISS neurones may modulate the LH surge. Although there is little evidence for the ARN to be involved in the timing of the LH surge, recent studies have suggested that the ARN KISS neurones may be involved in regulating the amplitude of the LH surge, potentially through direct projections to preoptic area kisspeptin neurones …”
Section: Discussionmentioning
confidence: 99%
“…35 Hence, it is possible that there is no direct or substantial circadian modulation of the different ARN KISS neurone sub-populations. involved in regulating the amplitude of the LH surge, 39,40 potentially through direct projections to preoptic area kisspeptin neurones. 41 In summary, these studies reveal marked sex-and subregionspecific effects of two neuropeptides on ARN KISS neurones.…”
Section: Discussionmentioning
confidence: 99%